GENERAL RULES OF ETIQUETTE OF COMMUNITY MEMBERS IN SCHOOLCHILDREN - Yunusalieva Nargiza Ortiqboy qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, students will learn about the general rules of schoolchildren’s morality and the impact of low-level "mass culture" on the younger generation, ideas that are completely alien to our national identity, worldview and thinking, artificial "values". and traditions”, in a word, spiritual threats. the need to preserve and form our national traditions in the minds of schoolchildren.